Selecting the best-value biosimilar in emerging countries - Gilberto Castañeda-Hernández (Exploration of Musculoskeletal Diseases, 2024)
The aim of biosimilars is to alleviate the financial burden of biological medicinal products. A most relevant challenge for emerging countries is how to select the best option available. In most cases, price is the major determinant, as budgets are chronically scarce. However, initial savings due to price reductions can be overridden if there is a lack of supply due to product shortages or withdrawals. These events can be prevented by a best-value strategy. According to the concept of best-value medicinal products, price is only one of the various criteria to be considered. The purpose of the present paper is to provide suggestions of criteria that can be useful for selecting the best-value biological in emerging countries. Six criteria, that are not limitative, have been selected as follows: standards of regulatory approval, quality of the product, good distribution practices, security of supply, pharmacovigilance, and price.